Integral equation methods for electromagnetics - Volakis, John Leonidas 1956-; Sertel, Kubilay (SciTech Publishing, 2012)
This text/reference is a detailed look at the development and use of integral equation methods for electromagnetic analysis, specifically for antennas and radar scattering. Developers and practitioners will appreciate the broad-based approach to understanding and utilizing integral equation methods and the unique coverage of historical developments that led to the current state-of-the-art. In contrast to existing books, Integral Equation Methods for Electromagnetics lays the groundwork in the initial chapters so students and basic users can solve simple problems and work their way up to the most advanced and current solutions. This is the first book to discuss the solution of two-dimensional integral equations in many forms of their application and utility. As 2D problems are simpler to discuss, the student and basic reader can gain the necessary expertise before diving into 3D applications. This is also the first basic text to cover fast integral methods for metallic, impedance, and material geometries. It will provide the student or advanced reader with a fairly complete and up-to-date coverage of integral methods for composite scatterers.